V alue Foundations of the Management Approach to Personality Education (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
The article examines conscious education, which is based on the management of the pedagogical process. The author analyzes the problem of management activities, which contributes to the development of society and personal education, achieving goals as a pedagogical value. The author identifies the problem of mastering the art of managing the educational process of students, which is an important pedagogical value.